Dimensions of Deaf/Hard-of-Hearing and Hearing Adolescents' Health Literacy and Health Knowledge. (1st August 2016) - Smith, Scott R.; Samar, Vincent J.
Abstract : Deaf and hard-of-hearing (D/HH) adults have lower health literacy compared to hearing adults, but it is unclear whether this disparity also occurs in adolescence. We used the Health Literacy Skills Instrument–Short Form (HLSI-SF), Short Form of the Test of Functional Health Literacy in Adults (S-TOFHLA), Comprehensive Heart Disease Knowledge Questionnaire (CHDKQ), and newly constructed interactive and critical health literacy survey items to quantify D/HH and hearing adolescents' health literacy. We adapted and translated survey materials into sign language and spoken English to reduce testing bias due to variable English language skills. Participants were 187 D/HH and 94 hearing college-bound high school students. When we adjusted for age, gender, race/ethnicity, school grade, and socioeconomic status, D/HH adolescents demonstrated weaker general and functional health literacy and cardiovascular health knowledge than hearing adolescents on the HLSI, S-TOFHLA, and CHDKQ (all p s < .0001). Standard health literacy or knowledge scores were associated with several interactive and critical health literacy skills (all p s < .05). D/HH adolescents who reported greater hearing-culture identity, having hearing aids, experiencing better hearing with assistive devices, having good quality of communication with parents, and attending hearing schools at least half of the time had higher functional health literacy (all p s < .025). Those who reported English as their best language and attending hearing schools at least half of the time had higher cardiovascular health knowledge scores (all p s < .03). Results suggest that interventions to improve D/HH adolescents' health literacy should target their health-related conversations with their families; access to printed health information; and access to health information from other people, especially health care providers and educators.